RESPONS VARIETAS DAN MUSIM TANAM TERHADAP PERTUMBUHAN, HASIL DAN KUALITAS JAMUR TIRAM - Deden Fatchullah; Ramdani Abdul Rahman; Endeh Masnenah (JURNAL AGROTROPIKA, 2020)
Oyster mushroom was a prospective vegetable commodity and has high economical value. The aim of this research was to find out oyster mushroom varieties that could be adapted in Bogor – West Java, and produced high yield and quality when cultivated both in the dry and rainy seasons. A Randomized Block Design with 4 replications were set up in mushroom houses during the dry and the rainy seasons. Treatments comprised of 6 varieties of oyster mushrooms, viz: varieties No. 1; 30; 37; 38; 46 (origin from IVEGRI’s collection) and No. 85 (origin from Bogor as control variety). The result showed that varieties and planting seasons has significantly effect on growth of oyster mushroom. However varieties has no significantly effect on yield of mushroom which was in average 55-91 ton/1000 m2 of mushrooms house area. Fresh yield of mushroom planted in dry season (91.3 ton) was significantly higher than those in wet season (61.7 ton). Varieties has significantly effect of mushroom quality, meanwhile seasons gave a same good quality with delicious/ ranking <3, storage resistance up to 2 days at room temperature and water content >90 %. Keywords: Planting season, Pleurotus ostreatus, growth, yield, quality